Inventory of Medicinal Plants for Pregnant and Postpartum Women in Dayak Tomun of The Lopus Village Lamandau Regency of Central Kalimantan - Eka Andy Santoso; Jumari Jumari; Sri Utami (Department of Biology, Faculty of Mathematics and Sciences, Semarang State University . Ro, 2019)
Dayak Tomun is a traditional society living in the Lamandau Regency of Central Borneo. The Dayak society Tomun has local wisdom in the treatment and care of pregnant women and the brithing process utilizies medicinal plants. The traditional medicines were passed down from the ancestors of the Dayak. The purpose of the research was to discover, assess, and inventory medicinal plant used in the treatment and care of pregnant and postpartum women by the Dayak Tomun. The method used was a semi-structured interview and direct participatory observation of six key informants professional activities in the treatment of Dayak Tomun in the Lopus Villages. As many as 17 species of medicinal plants with 14 families. Found of these 23.53% were of member of the family Zingiberaceae. Traditional herbal treatment of pregnant and postpartum by Dayak Tomun societies many are formulated by using part of the leaves (52%), boiled (37.50%) and consumed with a drink (28%). Treatment and care of pregnant and postpartum women in Dayak Tomun should be applied and preserved so that local knowledge of Dayak Tomun society in the Lopus Villages is not lost to the next generation. The research provided information to the society about the utilization of plants used in treatment for women.